Chromosomal localization of human glutamate receptor genes - McNamara, JO (J Neurosci, 1992)
The chromosomal localization of human glutamate receptor genes (GluR1- 4) has been established using PCR with DNA isolated from mapping panels of Chinese hamster-human hybrid cell lines and high-resolution fluorescent in situ suppression hybridization. This was accomplished with genomic clones containing putative human homologs of rat GluR 1–4 isolated by high-stringency screening of a cosmid library with the rat cDNAs encoding GluR1–4. The locations of GluR1–4, respectively, are 5q32–33, 4q32–33, Xq25–26, and 11q22–23. Evidence implicating glutamatergic synapses in a diversity of physiologic and pathologic processes together with concordance of the chromosomal locales and results of linkage analyses establishes GluR3 and GluR4 as candidate genes for a number of nervous system disorders including the oculocerebral-renal syndrome of Lowe and a form of manic-depressive illness.